2018
DOI: 10.1590/0102-672020180001e1360
|View full text |Cite
|
Sign up to set email alerts
|

Higher Values in Liver Elastography and Meld Score Are Mortality Predictors on Liver Transplant Waiting List

Abstract: Background: Liver elastography have been reported in hepatocellular carcinoma (HCC) with higher values; however, it is unclear to identify morbimortality risk on liver transplantation waiting list. Aim:To assess liver stiffness, ultrasound and clinical findings in cirrhotic patients with and without HCC on screening for liver transplant and compare the morbimortality risk with elastography and MELD score. Method: Patients with cirrhosis and HCC on screening for liver transplant were enrolled with clinical, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…High MELD score was significantly associated with the presence of HCC in the study participants. This finding has also been observed in other studies 19 . There could a bidirectional phenomenon; either underlying damaged liver was cause of raised MELD score as well as HCC or the presence of HCC has raised the MELD score at the time of calculation.…”
Section: Discussionsupporting
confidence: 91%
“…High MELD score was significantly associated with the presence of HCC in the study participants. This finding has also been observed in other studies 19 . There could a bidirectional phenomenon; either underlying damaged liver was cause of raised MELD score as well as HCC or the presence of HCC has raised the MELD score at the time of calculation.…”
Section: Discussionsupporting
confidence: 91%
“…One of them is TE, used for analysis of liver stiffness and steatosis. 5,10,19 In this study, we observed that the result obtained for liver stiffness by TE overestimates the stage of liver fibrosis and demonstrated low agreement between techniques, intermediate sensitivity, and intermediate specificity. It is worse for advanced fibrosis stages (F3/F4) compared to mild and intermediate cases.…”
Section: Discussionmentioning
confidence: 71%
“…[20]. These formulas represent the advantage of MELD-sodium in predicting the clinical course in the targeted group of patients, which is the objective and case-specific variables without the need for an observer [21].…”
Section: Introductionmentioning
confidence: 99%
“…The formulas for these scoring systems are as follows: MELD score = 3.78 × ln(serum bilirubin [mg/dL]) + 11.2 × ln(INR) + 9.57 × ln(serum creatinine [mg/dL]) + 6.43; MELD-Na score = MELD score + 1.59 (135 - Na) with maximum and minimum Na values of 135 and 120 mmol/L, respectively [ 20 ]. These formulas represent the advantage of MELD-sodium in predicting the clinical course in the targeted group of patients, which is the objective and case-specific variables without the need for an observer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%